Miniaturized bandstop frequency-selective structure using stepped-impedance resonators - Li, Bo (2013)
This letter describes a miniaturized bandstop frequency-selective structure (FSS) based on the stepped-impedance resonator (SIR). The FSS consists of a two-dimensional periodic array of vertical microstrip SIRs for thickness reduction. A shunt capacitor connecting the SIR center and ground is employed to widen the operating bandwidth and to improve the quasi-elliptic filtering response. It is shown that more than 40% thickness reduction of the FSS can be realized by choosing a small impedance ratio of the SIR, and a steep quasi-elliptic bandstop filtering performance is achieved by adjusting the value of the shunt capacitor. As an example, a prototype of the proposed FSS is designed, fabricated, and tested. The good agreement between simulated and measured results verifies the design concept of the miniaturized FSS.